Correlation of anthropometric sizes with blood presure, total cholesterole level, and blood fasting glucose level in young adult - Jenny Novina Sitepu (AcTion: Aceh Nutrition Journal, 2023)
Obesity and overweight raised cardiovascular disease risk through metabolic disfunction. Anthropometric is a simple and non invasive examination  that can be used to detect metabolic disorders. This study aimed to evaluated correlation of anthropometic sizes (BMI, WC, WHR, and skinfold) with systolic and diastolic blood pressure (BP), total cholesterol (TC), and fasting blood glucose (FBG). This cross sectional study involved 88 young adults as subject in 2019. Total cholesterol and fasting blood glucose was examined by digital rapid test, taken in the morning after 10-12 hours fasting. Datas were analyzed univariately to describe each variable. Then, datas were analyzed bivariately using Pearson correlation test for BMI, WC, WHR, TC, FBG, and Spearman rho test for skinfold and BP. The study showed that BMI correlated with dyastolic BP, and total cholesterol (p<0,05). WC correlated with systolic BP and diastolic BP (p<0,05). Biceps skinfold correlated with systolic BP, dyastolic BP, and total cholesterol (p<0,05). Triceps skinfold correlated with systolic BP, dyastolic BP, and total cholesterol (p<0,05). Suprailiaca skinfold correlated with systolic BP, dyastolic BP, and total cholesterol (p<0,05). In Conclusion, anthropometric can be used as predictor of total cholesterol level and blood pressure in young adult subjects.